Um agente reativo jogador de futebol: teoria e desenvolvimento - Alvares, Luis Otávio Campos (2001)
The RoboCup initiative is a challenge about soccer game, where AI and SMA researchers develop agent players that show a considerable level of competence in performing their tasks. The Soccerserver is the official robot soccer simulator used in the RoboCup. It allows the simulation of a soccer match and the evaluation of different techniques of MAS. The purpose of the present work is to show a reseach on a team architecture and the development of an agent for the Soccerserver simulator. We present a general outline about the individual agent architecture, its main caracteristics, agent skills and the especification of the agent player behavior.